2015
DOI: 10.1080/10402004.2014.990594
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of an Aluminum Matrix Composite with Al4SiC4Reinforcement under Dry Sliding Condition

Abstract: In the present research work, an aluminum-based metal matrix composite with in situ Al 4 SiC 4 particles has been developed by the incorporation of TiC particles in commercial aluminum melt through a stir-casting method. Microstructure evaluation in correlation to developed hardness and mechanical properties was performed. Furthermore, the dry sliding wear behavior of commercial aluminum and commercial aluminum-5 vol% Al 4 SiC 4 composite was investigated at low sliding speed (1 ms ¡1 ) against a hardened EN 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For the higher applied load, the increase in interfacial temperature is developed between the disc counter face and specimen surface due to their higher frictional contact. This causes increased the wear rate and COF [25]. Figures 11(c) and (d) depicts the optimum condition of the worn out surface of Al7075 alloy −10 wt% TiO 2 composite by applying load of 9.81 N, sliding velocity of 2.82 m s −1 , sliding distance of 1000 m. From the images, it can be noticed that the small cavities and cracks are visible on the surface of the composite.…”
Section: Regression Equationmentioning
confidence: 96%
“…For the higher applied load, the increase in interfacial temperature is developed between the disc counter face and specimen surface due to their higher frictional contact. This causes increased the wear rate and COF [25]. Figures 11(c) and (d) depicts the optimum condition of the worn out surface of Al7075 alloy −10 wt% TiO 2 composite by applying load of 9.81 N, sliding velocity of 2.82 m s −1 , sliding distance of 1000 m. From the images, it can be noticed that the small cavities and cracks are visible on the surface of the composite.…”
Section: Regression Equationmentioning
confidence: 96%
“…The effects of both applied load and sliding velocity were investigated as a function of percentage of silicate with fly ash in aluminum alloy. The wear rate of the LM24/4 wt.% fly ash and varying wt.% of silicate hybrid composite is influenced by the load (15,30,45,60, and 75 N) under sliding velocity (0.75, 1.5, 2.25, and 3 m/sec) which is illustrated in Figures 2(a)-2(d). When increasing the load 15 to 75 N, a similar trend in wear rate could be observed.…”
Section: Tribology Study Of Aluminum Hybridmentioning
confidence: 98%
“…It was concluded that the incorporation of graphite as primary reinforcement increased the wear resistance of composites and the inclusion of alumina as a secondary reinforcement also had a significant effect on the wear behavior. Kumar et al [15] developed Al 4 SiC 4 using in situ incorporation of TiC particles into commercial aluminum melt through stir casting method. The overall wear rate increased with load in alloy as well as in the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Gomes et al and Rajeev et al confirms that under optimum conditions, Al-Si alloys frictional force and wear rate increases with increase in load [15,16] whereas under the influence of higher sliding speeds, a non-linear decrease in wear properties are observed [17,18]. As steel is the widely used material and aluminium is the successor, the aluminium-steel tribo-pair is preferred for studying wear [19]. Liu et al concludes that the alloy wear is mainly caused by several wear mechanisms such as melt lubrication wear, oxidation wear, delamination wear, and seizure.…”
Section: Introductionmentioning
confidence: 96%